2018
DOI: 10.1109/tbcas.2018.2868746
|View full text |Cite
|
Sign up to set email alerts
|

Multiplierless Implementation of Noisy Izhikevich Neuron With Low-Cost Digital Design

Abstract: Fast speed and high accuracy implementation of biological plausible neural networks are vital key objectives to achieve new solutions to model, simulate and cure the brain diseases. Efficient hardware implementation of Spiking Neural Networks (SNN) is a significant approach in biological neural networks. This paper presents a Multiplierless Noisy Izhikevich Neuron (MNIN) model, which is used for digital implementation of biological neural networks in large scale. Simulation results show that the MNIN model rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…In another research, authors have presented a Multiplier less Noisy Izhikevich Neuron (MNIN) model, which was used for digital implementation of Biological neural networks in large scale. Simulation results have shown that the MNIN model reproduces the same operations of the original noisy Izhikevich neuron [4]. In another paper, authors have performed numerical simulations of synaptically coupled Izhikevich networks under the effect of general non-Gaussian Lvy noise.…”
Section: Introductionmentioning
confidence: 99%
“…In another research, authors have presented a Multiplier less Noisy Izhikevich Neuron (MNIN) model, which was used for digital implementation of Biological neural networks in large scale. Simulation results have shown that the MNIN model reproduces the same operations of the original noisy Izhikevich neuron [4]. In another paper, authors have performed numerical simulations of synaptically coupled Izhikevich networks under the effect of general non-Gaussian Lvy noise.…”
Section: Introductionmentioning
confidence: 99%
“…It is mentioned that in our proposed hardware, the LCU module is applied to calculates the power‐2 based function Ynew. In this case, we used the LCU module that is presented in Haghiri et al…”
Section: Digital Hardware Design (Dhd)mentioning
confidence: 99%
“…C, The proposed multiplierless implementation of VCC. D, Hardware realization of the Ynew based on the LCU module [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Digital Hardware Design (Dhd)mentioning
confidence: 99%
See 2 more Smart Citations